Pengaruh Pajak Daerah, Retribusi Daerah, dan Lain-Lain Pendapatan yang Sah Terhadap Pendapatan Asli Daerah Kota Payakumbuh Tahun 2013-2022 - Junaidi, Junaidi; Adriani, Zulfina; Yudi, Yudi; Widiastuti, Fitri; Sagita, Dora (Jurnal Paradigma Ekonomika, 2023)
This study aims to formulate programs and strategies for strengthening and developing human resources (HR) at Universitas Jambi, focusing on educational staff. The data utilized include both secondary and primary sources. Secondary data, including archives, documents, reports, and relevant statements, were collected through documentation. Primary data were obtained through Focus Group Discussions (FGD) to capture direct perspectives from stakeholders. Data were analyzed both qualitatively and quantitatively. Qualitative analysis utilized content analysis techniques to evaluate data from the FGDs. This analysis aimed to identify key themes, patterns, and insights from the collected data. Quantitative analysis employed descriptive statistics to provide an overview of the current human resource conditions and projections for the next five years. Based on a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the university's HR development vision and mission, it was found that Universitas Jambi is in a strategic position to strengthen and develop its human resources. Despite major strengths such as a diverse range of study programs and faculty qualifications, some weaknesses need to be addressed, including a faculty shortage in some areas and the need for curriculum updates. Opportunities for growth through collaboration and innovation in teaching and research are significant, yet faced with challenges such as academic competition and budget constraints. Recommendations for Universitas Jambi include: (1) focusing on the development of faculty and staff competencies through ongoing training and further education; (2) updating the curriculum to reflect labor market needs and advancements in knowledge; (3) enhancing infrastructure and resources to support innovation in learning and research; (4) implementing policies that promote inclusivity and diversity; (5) expanding partnerships with industry and other academic institutions; and (6) applying effective risk management strategies to address barriers in implementing HR development programs.